Interview with Maria José Hidalgo de la Vega: Romanization, power and ideology in Roman Northern Africa - Hidalgo de la Vega, Maria José (Romanitas - Revista de Estudos Grecolatinos, 2014)
Interview with Maria José Hidalgo de la Vega.